Time course of in vitro maturation of intra-erythrocytic malaria parasite: a comparison between Plasmodium falciparum and Plasmodium knowlesi - SD Srinivas (Memórias do Instituto Oswaldo Cruz., 2002)
The schizont maturation assay for in vitro drug sensitivity tests has been a standard method employed in the global baseline assessment and monitoring of drug response in Plasmodium falciparum. This test is limited in its application to synchronous plasmodial infections because it evaluates the effect of drug on the maturation of parasite especially from ring to schizont stage and therefore synchronized P. falciparum cultures are required. On the other hand, P. knowlesi, a simian malaria parasite has a unique 24-h periodicity and maintains high natural synchronicity in monkeys. The present report presents the results of a comparative study on the course of in vitro maturation of sorbitol synchronized P. falciparum and naturally synchronous P. knowlesi. Ring stage parasites were incubated in RPMI medium supplemented with 10-15% pooled homologous serum in flat-bottomed 96-well micro plates using a candle jar at 37°C. The results suggest that the ideal time for harvesting the micro-assay plates for in vitro drug sensitivity test for sorbitol-synchronized P. falciparum and naturally synchronous P. knowlesi are from 26 to 30 h and from 22 to 25 h, respectively. The advantages of using P. knowlesi in chemotherapeutic studies are discussed.